Analisis Kesalahan Mahasiswa dalam Mengerjakan Latihan Soal Materi Ring pada Mata Kuliah Struktur Aljabar: Sebuah Kajian Mendalam Tentang Faktor-Faktor Yang Memengaruhinya - Sri Lestari Manurung; Beby Nadia Nasution; Desti Rahel Ayunda Sihotang; Samudera Efendi Marpaung (Departement of Mathematics Education, 2024)
This study is motivated by the presence of mistakes in solving Algebraic Structure problems, particularly on the topic of Ring. The purpose of this research is to analyze the mistakes made in solving Algebraic Structure problems, specifically on the topic of Ring at Universitas Negeri Medan. Mistakes are classified into conceptual errors, data usage errors, language interpretation errors, technical errors, and conclusion errors. The research method used is descriptive qualitative, involving three sixth-semester students of the academic year 2024/2025 with prior knowledge of the Ring topic. Data collection techniques included tests and open questionnaires. Data analysis was conducted through data reduction and categorization of error types. The results show various errors such as conceptual errors, technical errors, and conclusion errors. This research can serve as a recommendation for educators to be more proactive in assisting students in understanding the material through more effective and engaging teaching methods, as well as providing more in-depth training.